Strategi Pencegahan Kejahatan Penculikan Anak Pada Saat Aktivitas Pulang Sekolah - Ni Luh Gede Yogi Arthani (Satya Dharma : Jurnal Ilmu Hukum, 2021)
Protection of children is not only an activity and effort of the parents whose obligation to protect their children, but also the effort of all levels of society. The community and the state are obliged to participate in child protection because children are the successors of the nation. The crime of kidnapping children is prone to occur in children who are outside the supervision of parents or the environment of people who care about children, one of the opportunities that is often used by perpetrators to kidnap children is when they come back home from their school. This research is a normative juridical research, by formulating problems namely: 1) What are the factors that cause the crime of kidnapping children after school? 2) What is the strategy in preventing the crime of kidnapping children during activities after school? Factors that cause child abductions are due to the opportunity and negligence of parents or guardians of children in supervising children. Therefore, to prevent kidnapping of children during activities after school, there needs to be cooperation of parents, children, schools, and government participation through the police together to look after and provide protection to children, to prevent kidnapping of children.